Welt - Zeit - Theater: Neun Untersuchungen zum Werk von Bernd Alois Zimmermann. - Korte, Oliver, (Georg Olms Verlag, 2018)
2018 sees the centenary of the birth of Bernd Alois Zimmermann. His works have become part of the repertoire, young composers refer to him, and his work is increasingly attracting scholarly attention.